مساهمة في دراسة بيوستراتغرافية ترسيبية لتوضعات طابق السينومانيان في الجزء الجنوبي من السلسلة الساحلية السورية ( رقعتي طرطوس- صافيتا 1/50000) (Latakia University Journal -Basic Sciences Series, 2017)
تمت دراسة 30 عينة رسوبية بالإضافة إلى دراسة عينات متنوعة عديدة في الحقل تابعة للسينومانيان في رقعتي طرطوس وصافيتا .دلت النتائج على وجود صدوع عديدة محلية وثانوية لها صلة بالصدع المشرقي، ساهمت في تشقق الصخور الكربوناتية رقيقة التطبق، مما سهل استثمار المقالع الحجرية في المنطقة.أشارت هذه الدراسة إلى أن طبقات السينومانيان تتمثل بدورات رسوبية تتناوب فيها الرسوبيات العميقة التوضع مع الضحلة، ووجود طبقة غضارية داكنة اللون في تشكيلة صلنفة جديرة بالاهتمام، ومظاهر ترسيبية داخل الصخور الكلسية والكلسية المارنية وأخرى مستحاثية تستحق الدراسة ، كالعقد الصوانية والكلسية وغيرها. دلت دراسة بعض هذه العقد الصوانية احتواءها على قواقع الروديست ، كما دلّ بعضها الآخر احتواءه على المنخربات القاعية مثل Orbitolina في تشكيلة الحنفية ؛ التي تدل على الترسيب والتشكل في وسط بحري ضحل.مكّنت الدراسة الباليونتولوجية تأكيد نسب المنطقة المدروسة إلى طابق السينومانيان، من خلال المستحاثات المجهرية / المنخربات/ والجهرية، حيث تمثلت الأخيرة ببعض معديات الأرجل والأمونيتات وصفيحيات الغلاصم، كما تم تحديد طبقة أوستر Oyster مرشدة في المنطقة لتشكيلة الحنفية وكذلك طبقة الروديست Rudista. أظهرت هذه النتائج تابعية التوضعات للمناطق الرسوبية من نمط السطيحات الكربوناتية Carbonate-Platform.Study of 30 sediment samples at the laboratory and different Samples in situ (Field observation) reveals that related to Cenomanian Stage in Tartus and Safita Area.The results of this study reveals there are many, secondary and local Faults, which are related to the east Mediterranean mean Fault, which contributed in the exist joints in carbonate thin deposit Rocks, which help in quarrying the rocks.The study reveals that the cenomanian strata are represented by Deeping / shallowing-up Cycles and an interesting darkish mud sedimentary layer in Slenfa formation, and there are some other interesting sedimentary limestone and marly limestone's deposits, which contain fossils and some flint nodules and nodular limstone. The study of some of these flint nodules indicated the existent of rudistic shell within it, where as the other contain some benthic Foraminifera as Orbitolina, which reveals an Sedimentation in shallow marine environment.The study of fossils, micro Foraminifera & macro, in rock samples have prove that sedimentary rocks in the study area are related to the Cenemanian stage. The macro fossils like (Gastropods, Bivalves & Ammonites ), also we determined a layer of Oyster in the area within Hanafiah formation and Rudista layer. Result revealed that sediment deposit related to Carbonate-Platform.